New Host Record of The Yellow Steam Borer Moths, Scirpophaga incertdas Shall (Lepidoptera: Pyralidae) - Sutrisno, Hari (Perhimpunan Biologi Indonesia, 2007)
SHORT COMUNICATIONNew Host Record of The Yellow Steam Borer Moths, Scirpophagaincertdas Shall (Lepidoptera: Pyralidae)